The Role of Schema Therapy and Cognitive–Behavioral Therapy in Reducing Alexithymia in Maladjusted Couples: A Comparative Study - Saroukhani, Fatemeh; Shafiabadi, Abdollah; Ghodrati, Sima (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to compare the effectiveness of schema therapy and cognitive–behavioral therapy (CBT) in reducing alexithymia in maladjusted couples. Methods and Materials: This applied, quasi-experimental study employed a pretest–posttest design with a control group and a two-month follow-up. The statistical population comprised couples who referred to psychology clinics in District 2 of Tehran during the first half of 2025 due to marital conflict. Using convenience sampling, 45 couples were recruited and randomly assigned to three groups: schema therapy (n = 15), cognitive–behavioral therapy (n = 15), and a control group (n = 15). Following attrition of one couple from the CBT group, analyses were conducted on 44 couples. The experimental groups received ten sessions of their respective interventions, while the control group received no treatment during the study period. Data were collected using the Toronto Alexithymia Scale (TAS-20) at pretest, posttest, and follow-up, and analyzed using repeated-measures analysis of variance. Findings: Repeated-measures ANOVA revealed a significant main effect of time on alexithymia scores (p < .001) and a significant interaction effect between group and time (p < .001). Post hoc comparisons indicated that both schema therapy and CBT produced significant reductions in alexithymia from pretest to posttest (p < .001). However, schema therapy resulted in significantly greater reductions than CBT at posttest (p < .01), and these effects remained significantly more stable at the two-month follow-up (p < .01). No significant changes were observed in the control group across measurement points (p > .05). Conclusion: Both schema therapy and cognitive–behavioral therapy are effective in reducing alexithymia among maladjusted couples, but schema therapy demonstrates superior effectiveness and greater durability of outcomes, suggesting that emotion-focused and schema-based interventions may be particularly beneficial for couples with pronounced emotional processing deficits.